Responsible microservices (O'Reilly, 2019)
"These days, you can't swing a dry-erase marker without hitting someone talking about microservices. Developers are studying Eric Evans's prescient book Domain-Driven Design. Teams are refactoring monolithic apps, looking for bounded contexts, and defining a ubiquitous language. And while there have been countless articles, videos, and talks to help you convert to microservices, few have spent any appreciable time asking if a given application should be a microservice. Nathaniel Schutta (Pivotal) shows you a set of factors you can apply to help you decide if something deserves to be a microservice or not. You'll also look at what you need to do to maintain a healthy micro(services)biome. This session was recorded at the 2019 O'Reilly Software Architecture Conference in San Jose."--Resource description page